Ekspektasi Guru dan Resiliensi Remaja - Sayyida Syal Sabila; Lailatuzzahro Al-Akhda Aulia (Ilmu Psikologi Universitas Yudharta Pasuruan)
The result of observation in some teenagers who have entering high school while living in the dormitory, will have many demands that must be done. Students who adjust to all kinds of tasks that must be done will feel depressed and stress, so the students need a resilience to can rise from the stress conditions. The existence of resilience will turn the problem into a challenge, failure to success, and powerlessness to power. This study aims to determine the relationship of teacher expectations with adolescents resilience. The population in this research is class X MAN 2 Pasuruan, with the sampling technique is cluster random sampling. Data collection using resilience scale with validity between 0,328 until 0,555 with reliability 0,8480 and teacher expectation scale obtained validity between 0,320 until 0,552 with reliability 0,8546. The results showed that teacher expectation have relationship with adolescents resilience, with rxy 0,669 > r-table 1% 0,230. Freg 80,5929 > F-tab 1% 6,63. Thus there is a very significant relationship on teacher expectations with adolescents resilience.